Acute glans ischemia after circumcision successfully treated with low-molecular-weight heparin and topical dihydrotestosterone: A case report. Issue 29 (17th July 2020) - Zvizdic, Zlatan; Anic, Dusko; Popovic, Nusret; Vranic, Semir
Abstract: Rationale: Circumcision like any other surgical procedure is not devoid of complications. Serious complications are rare and include iatrogenic hypospadias, glans ischemia/necrosis, and glans amputation, all of which require an emergent treatment. Patient concerns: We report here a case of 6 months-old-boy with a superficial glans ischemia following circumcision. Diagnosis: Physical examination revealed a severely cyanotic glans with the moderate edema of the dorsal penile skin. Plasma levels of D-dimer were 8.57 mg/L. Urine passage was unremarkable while color Doppler ultrasonography revealed a normal blood flow. Interventions: The patient was successfully treated with subcutaneous injection of enoxaparin (low-molecular-weight heparin) and topical 2.5% dihydrotestosterone. Outcomes: The appearance of the glans penis on the 5th day was close to normal while the control levels of D-dimer dropped to the reference range. The patient was discharged from the hospital on the 6th day. At 6-month follow-up, the appearance of the glans penis was normal. Lessons: Acute glans penis ischemia following circumcision is a rare complication. Its successful treatment with enoxaparin and topical dihydrotestosterone has not been previously reported in the literature.